Achievements of the Bologna process reforms: an integrated management and IT approach - Velada, R.; Cardoso, E.; Antunes, Ana; Caetano, António; Bento, Rui; Aguiar, Francisco; Silva, S.A.; Sequeira, Manuel Menezes de (15th International Conference on European University Information Systems (EUNIS 2009), 2009)
In this paper we will describe a national perspective on the achievements of the Bologna Process in Portugal regarding the academic years of 2006/2007 and 2007/2008, and detail the approach followed at the Lisbon University Institute (ISCTE-IUL). The main objective of the paper is to describe the joint initiative that has been developed at ISCTE-IUL to implement a Decision Support System (DSS) that will enable the collection, analysis and dissemination (through reporting) of the required performance indicators to render possible an automatic elaboration of these reports. The paper will focus on the requirements gathering phase of the decision support system designed to enable the automatic generation of Bologna reports. This DSS constitutes a research project and is being developed with the sponsorship of the Computer Center (DSI) and Quality Assurance and Evaluation Office (GAQE), integrated with the University’s information system Fénix (based on FénixEDU®).